FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI WAKTU KERJA WANITA PENJEMUR IKAN ASIN DI KECAMATAN KAMPUNG MELAYU KOTA BENGKULU - Mohamad Zulkarnain Yuliarso; Gita Mulyasari; Kholijah Nst (Universitas Mataram, 2024)
The role of women has a reasonably high impact in helping their family's economy. All activities often carried out by women have their economic value. This research aims to (1) Analyze the time allocation of women drying salted fish and (2) Analyze the factors that influence the work time allocation of women drying salted fish in Kampung Melayu District, Bengkulu City. This research was conducted in Kampung Melayu District, Bengkulu City, with 55 women drying salted fish selected using census techniques. (non-probability sampling). The descriptive analysis calculates the time allocation of women drying salted fish, including productive, domestic, social, and leisure time. To analyze the factors that influence women's work time allocation, a multiple regression model was used with the independent variables consisting of age, education level, number of family dependents, work experience, husband's acceptance, and the presence of toddlers. The research results show that more time is allocated to women drying salted fish in Sumber Jaya Village for leisure, domestic, productive, and social time. Husband's acceptance and the presence of toddlers influence the work time allocation of women drying salted fish.